Effects of Corrective Feedback on Students’ Linguistic Errors - Nirwana AR (Universitas Muhammadiyah Mataram, 2018)
The research aimed at finding out (i) Whether corrective feedback could minimize students’ linguistic error; (ii) Which type of corrective feedback had more permanent effect on students’ writing accuracy. The research applied single-subject experiment design. Data analysis in single-subject research typically was based on visual inspection and analysis of graphic presentation. The step are writing test, ratio, scoring and compare. In this study, six treatment groups and no control group were used. All treatment groups received in different types of CF on their writing tests. Treatment 1 (T1) received Direct CF, treatment 2 (T2) received indirect CF, treatment 3 (T3) received metalinguistic CF, treatment 4 (T4) received reformulation CF, treatment 5 (T5) received focused CF, Treatment 6 (T6) received unfocused CF. The findings indicated that (i) CF could minimize students’ linguistic errors except focused CF on vocabulary; (ii) Based the result of the data analysis using analytic rating scale and composite rating scale showed that direct CF had the most effective in minimizing students’ linguistic error in vocabulary, language use and mechanics than the other types of CF, so direct CF could be categorized having more permanent effect on students’ writing accuracy.